Copper-zinc-zirconium-silicon catalyst with hydrophobic surface as well as preparation method and application of copper-zinc-zirconium-silicon catalyst
By adding hydrophobic silica to the copper-based catalyst and using ZrO2 as a support, the problems of reducing activity of the copper-based catalyst and the generation of by-products in the CO2 hydrogenation reaction are solved, and a copper-zinc-zirconium silicon catalyst with high catalytic activity, selectivity and stability are achieved.
Patent Information
- Application Number
- CN202411711292.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing copper-based catalysts have high anti-water gas conversion reaction activity in the CO2 hydrogenation reaction, resulting in sintering and inactivation of the catalyst, reducing activity, and reducing the selectivity of methanol by-product CO.
Using a copper-zinc-zirconium silicon catalyst with a hydrophobic surface, the wetting of water is adjusted by adding hydrophobic silica to the catalyst surface, the diffusion rate of by-product water is increased, the concentration of water vapor on the catalyst surface is reduced, and ZrO2 is used as a support to improve the water heat resistance of the catalyst.
It improves the stability and selectivity of the catalyst, enhances the catalytic activity, reduces the generation of by-products, and extends the service life of the catalyst.
Smart Images

Figure CN119524860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper-zinc-zirconium-silicon catalyst with a hydrophobic surface, a preparation method thereof and an application thereof. Background Art
[0002] With the acceleration of economic development, CO2 emitted by industrial production has attracted increasing attention. The "greenhouse effect" and "ozone hole" caused by it affect the harmonious coexistence of humans and nature. Carbon dioxide (CO2) is the main greenhouse gas and an abundant renewable resource. Through catalytic conversion, carbon dioxide can be directed into chemicals, energy products and functional materials, that is, realizing the resource utilization process of "turning waste into treasure and high-value utilization".
[0003] The synthesis of methanol by catalytic hydrogenation of CO2 is one of the hot topics in the field of C1 chemistry, and has multiple significances in chemical industry, environmental protection and economy. At present, the most mature carbon dioxide hydrogenation to methanol is copper-based catalyst represented by copper-zinc-zirconium system. However, in the CO2 hydrogenation reaction, due to the high reverse water-gas shift reaction activity of copper-based catalysts, a large amount of water will be produced during the reaction, and water will accelerate the sintering and deactivation of the catalyst, reducing the catalytic activity; at the same time, a large amount of by-product CO will be generated in the reaction, which will reduce the methanol selectivity.
[0004] CN 116637624A discloses a method for preparing a Cu / ZnO / SiO2 composite catalyst, in which a silicon dioxide surface coating layer is added during the catalyst preparation process to inhibit the generated water from entering the catalyst surface and contacting the copper-based catalyst, thereby protecting the copper-based catalyst from being oxidized by the water generated during the methanol synthesis process, but the CO2 conversion rate during the reaction is low. CN 116393160A discloses a method for preparing a copper-zinc-aluminum-molecular sieve catalyst for catalyzing CO2 hydrogenation to methanol, in which a hydrophobic molecular sieve is prepared by a solid phase synthesis method, and finally a catalyst for combined use is obtained by physically mixing and filling the copper-zinc-aluminum catalyst and the molecular sieve. Based on the hydrophobic property of the hydrophobic molecular sieve, the concentration of water vapor on the catalyst surface can be effectively reduced, thereby improving the stability of the catalyst, but the method has relatively complicated operation steps, and some reaction conditions are not suitable for large-scale industrial production. Summary of the invention
[0005] The present invention is made to solve the above-mentioned problems, and aims to provide a copper-zinc-zirconium-silicon catalyst with a hydrophobic surface, a preparation method and an application thereof. The preparation method of the copper-zinc-zirconium-silicon catalyst is simple, the reaction conditions of the preparation process are mild, the cost is low, and it is suitable for industrial large-scale production. The copper-zinc-zirconium-silicon catalyst has high catalytic activity, selectivity and stability when catalyzing the hydrogenation of carbon dioxide to produce methanol.
[0006] The first aspect of the present invention provides a copper-zinc-zirconium-silicon catalyst having a hydrophobic surface, characterized in that it comprises the following components measured in terms of amount:
[0007] (1) 50 to 60 parts of copper or copper oxide, calculated as copper element;
[0008] (2) 20 to 30 parts of zinc or zinc oxide, calculated as zinc element;
[0009] (3) 8 to 20 parts of zirconium or zirconium oxide calculated as zirconium element;
[0010] (4) 8 to 20 parts of hydrophobic silica calculated as elemental silicon.
[0011] The present invention uses copper as the active component of the catalyst, and the Zn atoms in the added zinc or zinc oxide can form active sites, so that the reduced Cu atoms are evenly embedded in the ZnO lattice structure, and produce a strong synergistic effect with ZnO, greatly enhancing the reaction activity and stability of the catalyst.
[0012] Furthermore, the traditional copper-zinc-aluminum methanol catalyst is easily deactivated during the CO2 hydrogenation reaction, mainly because the metal copper particles agglomerate under the synergistic effect of high temperature and water vapor generated by the reverse water gas reaction, resulting in reduced catalyst activity. The present invention adjusts the wettability of water on the surface of the copper-zinc-zirconium-silicon catalyst by adding hydrophobic silica, accelerates the diffusion rate of the byproduct (water) during the reaction, and can effectively reduce the concentration of water vapor on the surface of the copper-zinc-zirconium-silicon catalyst during the reaction, thereby improving the stability of the copper-zinc-zirconium-silicon catalyst.
[0013] Furthermore, conventional catalysts usually use Al2O3 as a catalyst carrier, while the present invention uses ZrO2 as a carrier based on the design principle of improving the hydrophobicity of the copper-zinc-zirconium-silicon catalyst. ZrO2 has stronger hydrophobicity than Al2O3, thereby further improving the hydrothermal resistance of the copper-zinc-zirconium-silicon catalyst. Zirconium or zirconium oxide can evenly disperse the active components of the catalyst, so that the catalyst has higher activity, selectivity and stability.
[0014] The second aspect of the present invention provides a method for preparing a copper-zinc-zirconium-silicon catalyst having a hydrophobic surface, characterized in that it comprises the following steps:
[0015] (1) mixing a copper nitrate solution, a zinc nitrate solution, and a zirconium nitrate solution with a precipitant and then aging the mixture, and then mixing the mixture with a surfactant to obtain a copper-zinc-zirconium catalyst solution; the mixing ratio of the copper nitrate solution, the zinc nitrate solution, and the zirconium nitrate solution is such that the molar ratio of the copper element, the zinc element, and the zirconium element is 1:(0.2-1):(0.1-0.5) in terms of elements;
[0016] (2) mixing the silica sol with a hydrophobic agent, adding an ammonia solution to modify and hydrolyze the silica sol to obtain a hydrophobic silica sol;
[0017] (3) Mixing the copper-zinc-zirconium catalyst solution described in step (1) with the hydrophobic silica sol described in step (2), drying and then calcining to obtain the copper-zinc-zirconium-silicon catalyst.
[0018] Compared with traditional catalysts, which usually use Cu or Cu / ZnO as an active interface and are isolated in a specific silica structure, Cu or Cu / ZnO is prone to migration and aggregation during the reaction. In the process of mixing the copper-zinc-zirconium catalyst solution with the hydrophobic silica sol, the present invention makes the copper-zinc-zirconium catalyst evenly dispersed in the hydrophobic silica sol, and controls the hydrophobic silica sol to continuously gel, and uses the three-dimensional network structure formed by the hydrophobic silica gel to restrict Cu-ZnO-ZrO2, so that the metal Cu and the metal oxides ZnO and ZrO2 produce strong chemical bonds in the restricted three-dimensional network structure. This interaction can prevent the sintering and aggregation of Cu nanoparticles, that is, prevent the aggregation and growth of Cu nanoparticles at high temperatures, resulting in reduced catalyst activity. Through strong metal-carrier interaction, the nano-scale dispersion state of Cu is maintained, so that the number of active centers and active positions of the catalyst are evenly distributed, so that a more stable catalytic performance can be provided, and the prepared copper-zinc-zirconium-silicon catalyst has better catalytic stability.
[0019] In some embodiments, in step (1), the surfactant includes one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, and fatty alcohol polyoxyethylene ether, and the molar ratio of the added amount of the surfactant to the copper element is 1: (16-50).
[0020] In the embodiment, a copper-zinc-zirconium catalyst precursor prepared by mixing and aging a copper nitrate solution, a zinc nitrate solution, a zirconium nitrate solution and a precipitant is treated with a surfactant, which is beneficial for uniform dispersion of Cu, Zn and Zr components in the slurry, and then uniformly dispersed in the hydrophobic sol.
[0021] In some embodiments, in step (1), the concentrations of the copper nitrate solution, the zinc nitrate solution, and the zirconium nitrate solution are 0.1 to 5 mol / L, and the precipitant is an inorganic alkaline salt.
[0022] In some embodiments, in step (1), the aging temperature is 60°C to 90°C, the aging pH is 5 to 9, and the aging time is 30-90 min.
[0023] Aging temperature and time are important factors that affect the catalyst's chemical composition, physical phase, particle size, pore size distribution and other physical and chemical properties, which in turn affect the catalyst's microstructure and catalytic performance. Therefore, finding the optimal aging temperature and time so that the precursor generated in the previous precipitation process can be aged to form a catalyst with a suitable chemical composition, particle size and pore size distribution is one of the important contents that must be studied in the preparation of catalysts by precipitation method.
[0024] In some embodiments, the step (2) specifically comprises: diluting the hydrophobic agent with anhydrous ethanol to obtain a hydrophobic agent dilution solution, mixing the hydrophobic agent dilution solution with silica sol, and adding ammonia solution dropwise to control the pH to 5-9.
[0025] In the embodiment, the pH value of 5 to 9 is conducive to further hydrolysis of silica sol to generate silica gel. In some embodiments, in the step (2), the dilution volume ratio of the hydrophobic agent is 1% to 10%, and the volume ratio of the hydrophobic agent dilution liquid to the silica sol is (0.3 to 5): 1, and the hydrophobic agent includes one of perfluorononanoic acid, perfluoropolyether, perfluorodecyltrialkoxysilane, and perfluorooctyltrialkoxysilane.
[0026] In the embodiment, by controlling the amount of the hydrophobic agent added, it is ensured that the surface of the copper-zinc-zirconium catalyst has good hydrophobicity after the hydrophobic agent is added, and does not affect the contact reaction between the reaction gas molecules and the surface active components.
[0027] In some embodiments, in step (2), the preparation step of silica sol includes: dissolving siloxane in a mixed solution of ethanol and water, adding ammonia solution and stirring to obtain silica sol; the siloxane includes one of methyltriethoxysilane, ethyl orthosilicate, and methyl orthosilicate, the volume ratio of ethanol to water in the mixed solution of ethanol and water is (1-15):1, and the volume ratio of siloxane to the mixed solution of ethanol and water is (0.1-1):1.
[0028] Since the silica sol prepared by a mixed solution of ethanol and water can adjust the pH value by adding acid or alkali, which helps to control the stability of the silica sol and has high thermal stability, in the embodiment, siloxane is dissolved in a mixed solution of ethanol and water (different volume ratios of ethanol and water can affect the rate at which siloxane is hydrolyzed to form a sol).
[0029] At the same time, since the solubility of siloxane in ethanol is generally higher than that in water, and the presence of ethanol can reduce the side reaction of the direct reaction of siloxane with water, which helps to form a more stable silica sol, in the embodiment, the added volume of ethanol in the mixed solution of ethanol and water is controlled to be larger than that of water to ensure the full dissolution of siloxane, reduce the side reaction of siloxane, and promote the formation of silica sol particles by controlling the amount of water added.
[0030] In some embodiments, in step (3), the drying temperature is 50-100° C., the drying time is 6-15 hours, the roasting temperature is 200-500° C., and the roasting time is 2-6 hours.
[0031] The third aspect of the present invention provides an application of a copper-zinc-zirconium-silicon catalyst having a hydrophobic surface, characterized in that the copper-zinc-zirconium-silicon catalyst described in the first aspect or the copper-zinc-zirconium-silicon catalyst prepared by the preparation method described in the second aspect is used to catalyze the hydrogenation of carbon dioxide to produce methanol.
[0032] By implementing the above technical solution, the present invention has the following beneficial effects:
[0033] The preparation method of the present invention adjusts the wettability of water on the surface of the copper-zinc-zirconium-silicon catalyst by adding hydrophobic silica, accelerates the diffusion rate of the by-product (water) during the reaction, and can effectively reduce the concentration of water vapor on the surface of the copper-zinc-zirconium-silicon catalyst during the reaction, thereby improving the stability of the copper-zinc-zirconium-silicon catalyst.
[0034] Based on the design principle of improving the hydrophobicity of the copper-zinc-zirconium-silicon catalyst, the present invention adopts ZrO2 as a carrier. ZrO2 has stronger hydrophobicity than Al2O3, thereby further improving the hydrothermal resistance of the copper-zinc-zirconium-silicon catalyst.
[0035] In the process of mixing the copper-zinc-zirconium catalyst solution with the hydrophobic silica sol, the copper-zinc-zirconium catalyst is uniformly dispersed in the hydrophobic silica sol, and the hydrophobic silica sol is controlled to continuously gel. The three-dimensional network structure formed by the hydrophobic silica gel is used to restrict Cu-ZnO-ZrO2, so that the metal Cu and the metal oxides ZnO and ZrO2 generate strong chemical bonds in the restricted three-dimensional network structure. This interaction can prevent the sintering and aggregation of Cu nanoparticles, that is, prevent the Cu nanoparticles from aggregating and growing at high temperatures, resulting in reduced catalyst activity. Through the strong metal-carrier interaction, the nano-scale dispersion state of Cu is maintained, so that the number of active centers and active positions of the catalyst are evenly distributed, thereby providing a more stable catalytic performance and making the prepared copper-zinc-zirconium-silicon catalyst have better catalytic stability.
[0036] The preparation method provided by the present invention uses a surfactant to treat a copper-zinc-zirconium catalyst prepared by mixing and aging a copper nitrate solution, a zinc nitrate solution, a zirconium nitrate solution and a precipitant, so that a stable adsorption layer is formed on the surface of the copper-zinc-zirconium catalyst, which helps to enhance the interaction between Cu, ZnO and ZrO2, improve the stability and activity of the copper-zinc-zirconium catalyst in a non-aqueous medium, and further improve the adhesion and stability of the copper-zinc-zirconium catalyst in a hydrophobic sol, thereby improving the bonding degree between the two. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 11 is the XRD diagram of the catalysts prepared in various embodiments and comparative examples of the present invention. DETAILED DESCRIPTION
[0038] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.
[0039] Example 1
[0040] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Zr:Si=5.5:2.7:0.9:0.9.
[0041] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0042] (2) 4.7 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH=9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0043] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0044] Example 2
[0045] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Zr:Si=5.5:2.7:0.9:0.9.
[0046] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0047] (2) 4.7 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol to control the pH of the sol to pH = 8.0, so as to accelerate the hydrolysis of the sol and obtain a hydrophobic silica sol;
[0048] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0049] Example 3
[0050] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Zr:Si=5.22:2.61:0.87:1.30.
[0051] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0052] (2) 7.0 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH=9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0053] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0054] Example 4
[0055] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5.22:2.61:0.87:1.30.
[0056] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0057] (2) 7.0 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH=8.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0058] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0059] Example 5
[0060] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0061] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0062] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0063] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0064] Example 6
[0065] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0066] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0067] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol to control the pH of the sol to pH = 8.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0068] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0069] Example 7
[0070] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0071] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0072] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent and the silica sol were mixed evenly at a volume ratio of 3:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0073] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0074] Example 8
[0075] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0076] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0077] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent and the silica sol were mixed evenly at a volume ratio of 4:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0078] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0079] Example 9
[0080] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0081] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.0 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0082] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0083] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0084] Example 10
[0085] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0086] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 2.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0087] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0088] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0089] Comparative Example 1
[0090] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al=6:3:1.
[0091] Prepare 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Al(NO3)3·9H2O and Na2CO3 solutions, take 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of aluminum nitrate solution and mix them evenly, and take 200 ml of sodium carbonate solution at the same time. Use a peristaltic pump to drop the copper-zinc-aluminum salt mixed solution and the precipitant into a three-necked flask at 70°C at a rate of 15 ml / min to obtain a mixed slurry A; after aging the mixed slurry A at 80°C and pH=7.0 for 60 min, filter and wash to obtain a catalyst precursor wet material B, dry the catalyst precursor wet material at 110°C for 12 h, put it into a muffle furnace and calcine it at 350°C for 3 h to obtain a copper-zinc-aluminum catalyst.
[0092] Comparative Example 2
[0093] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0094] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol and 1.5 g of hexadecyltrimethylammonium bromide were added to the catalyst precursor wet material B, and the mixture was stirred for 15 min to obtain a copper-zinc-zirconium catalyst solution C;
[0095] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and after stirring for 15 min, a 0.8 mol / L ammonia solution was added dropwise to control the pH of the sol to pH = 9.0 to accelerate the hydrolysis of the sol to obtain a silica sol;
[0096] (3) After the above silica sol is added to the copper-zinc-zirconium catalyst solution C, the silica sol gradually begins to gel and finally forms silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the silica gel. The silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0097] Comparative Example 3
[0098] The molar ratio of the copper-zinc-zirconium-silicon catalyst components is Cu:Zn:Al:Si=5:2.5:0.83:1.67.
[0099] (1) 1.25 mol / L Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, Zr(NO3)4·5H2O and Na2CO3 solutions were prepared, 100 ml of copper nitrate solution, 50 ml of zinc nitrate solution and 17 ml of zirconium nitrate solution were mixed to obtain a copper-zinc-zirconium salt mixed solution, 200 ml of sodium carbonate solution was used as a precipitant, and the copper-zinc-zirconium salt mixed solution and the precipitant were simultaneously added dropwise to a three-necked flask at 70° C. at a rate of 15 ml / min using a peristaltic pump to obtain a mixed slurry A; the mixed slurry A was aged at 80° C. and pH=7.0 for 60 min, and then filtered and washed to obtain a catalyst precursor wet material B; 60 ml of ethanol was added to the catalyst precursor wet material B, and stirred for 15 min to mix them evenly to obtain a copper-zinc-zirconium catalyst solution C;
[0100] (2) 9.3 ml of ethyl silicate was added to a mixed solution of 15 ml of ethanol and 5 ml of deionized water, and the mixture was stirred for 15 min to obtain a silica sol; perfluorononanoic acid was diluted to 5% with anhydrous ethanol, and the diluent was mixed with the silica sol at a volume ratio of 2:5 to modify the silica sol, and a 0.8 mol / L ammonia solution was added dropwise to the silica sol, and the pH of the sol was controlled to be pH = 9.0 to accelerate the hydrolysis of the sol to obtain a hydrophobic silica sol;
[0101] (3) After the hydrophobic silica sol is added to the copper-zinc-zirconium catalyst solution C, the hydrophobic silica sol gradually begins to gel and finally forms a hydrophobic silica gel. The catalyst precursor in the copper-zinc-zirconium catalyst solution C is evenly dispersed in the hydrophobic silica gel. The hydrophobic silica gel with the copper-zinc-zirconium catalyst is dried at 60°C for 12 hours and then placed in a muffle furnace and calcined at 350°C for 3 hours to obtain a copper-zinc-zirconium silicon catalyst.
[0102] Performance Testing
[0103] The catalyst performance test was carried out in a fixed bed reactor. 1 mL of catalyst with a size of 20-40 mesh and 1 mL of quartz sand with the same mesh were measured, mixed evenly and loaded into the isothermal zone of the fixed bed reactor. The catalytic reaction conditions were a temperature of 250°C, a reaction pressure of 5 MPa, and a reaction volume space velocity of 10,000 h -1, the mixed reaction gas CO2 / Ar / H2=24:4:72, where Ar is the internal standard gas for gas chromatography analysis. The carbon dioxide and carbon monoxide in the gas phase products are quantitatively analyzed by online gas chromatography equipped with a TCD detector, and the compounds in the liquid phase products are quantitatively analyzed by online gas chromatography equipped with a FID detector. Finally, the carbon dioxide conversion rate and the methanol space-time yield are calculated. The catalyst evaluation process is as follows: the catalyst is tested for its initial activity under the reaction condition of 250℃. After a period of reaction, the temperature is increased to 380℃ to perform high-temperature treatment on the catalyst to accelerate its deactivation. After a period of heat resistance, the reaction temperature is lowered back to 250℃ to test its post-heat resistance activity. The percentage of post-heat resistance activity to initial activity is the heat resistance retention rate R, which is usually used to replace the life experiment.
[0104] The CO2 hydrogenation performance test results are listed in Table 1. The XRD patterns of the catalysts prepared in each embodiment and comparative example are shown in Table 1. Figure 1 shown.
[0105] Table 1 CO2 hydrogenation performance on different catalysts
[0106]
[0107]
[0108] It can be seen from Table 1 that the methanol yield and selectivity of the copper-zinc-zirconium-silicon catalyst in each embodiment of the present application are significantly higher than those of the reference catalyst in Comparative Example 1 without the addition of silica sol, and the heat retention rate and methanol yield are higher than those of the reference catalyst in Comparative Example 2 without the addition of a hydrophobic agent and in Comparative Example 3 without the addition of a surfactant. The copper-zinc-zirconium-silicon catalyst with hydrophobic and confined NPs prepared in the embodiments has higher catalytic activity, methanol space-time yield and life. At the same time, from Figure 1 It can be seen from the XRD diagrams of each catalyst that the CuO and ZnO diffraction peaks of the copper-zinc silica sol catalyst in each embodiment of the present application are more diffuse than those of Comparative Example 1, Comparative Example 2, and Comparative Example 3, and the peaks are short and wide, indicating that the crystallites are small.
[0109] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
Claims
1. A copper-zinc-zirconium-silicon catalyst having a hydrophobic surface, characterized in that: The components of the meter include the following substances: (1) 50 to 60 parts of copper or copper oxide, calculated as copper element; (2) 20 to 30 parts of zinc or zinc oxide, calculated as zinc element; (3) 8 to 20 parts of zirconium or zirconium oxide calculated as zirconium element; (4) 8 to 20 parts of hydrophobic silica calculated as elemental silicon.
2. A method for preparing a copper-zinc-zirconium-silicon catalyst having a hydrophobic surface as claimed in claim 1, characterized in that: The following steps are involved: (1) mixing a copper nitrate solution, a zinc nitrate solution, and a zirconium nitrate solution with a precipitant, and then aging the mixture, and then mixing the mixture with a surfactant to obtain a copper-zinc-zirconium catalyst solution; The mixing ratio of the copper nitrate solution, the zinc nitrate solution and the zirconium nitrate solution is 1:(0.2-1):(0.1-0.5) in terms of molar ratio of copper element, zinc element and zirconium element. (2) mixing the silica sol with a hydrophobic agent, adding an ammonia solution to modify and hydrolyze the silica sol to obtain a hydrophobic silica sol; (3) Mixing the copper-zinc-zirconium catalyst solution described in step (1) with the hydrophobic silica sol described in step (2), drying and then calcining to obtain the copper-zinc-zirconium-silicon catalyst.
3. The preparation method according to claim 2, characterized in that: In the step (1), the surfactant includes one of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, and fatty alcohol polyoxyethylene ether, and the molar ratio of the added amount of the surfactant to the copper element is 1: (16-50).
4. The preparation method according to claim 3, characterized in that: In the step (1), the concentrations of the copper nitrate solution, the zinc nitrate solution and the zirconium nitrate solution are 0.1 to 5 mol / L, and the precipitant is an inorganic alkali salt.
5. The preparation method according to claim 4, characterized in that: In the step (1), the aging temperature is 60° C. to 90° C., the aging pH is 5 to 9, and the aging time is 30 to 90 minutes.
6. The preparation method according to claim 2, characterized in that: The step (2) specifically comprises: diluting the hydrophobic agent with anhydrous ethanol to obtain a hydrophobic agent dilution solution, mixing the hydrophobic agent dilution solution with silica sol, and adding ammonia solution dropwise to control the pH value to 5-9.
7. The preparation method according to claim 7, characterized in that: In the step (2), the dilution volume ratio of the hydrophobic agent is 1% to 10%, and the volume ratio of the hydrophobic agent dilution liquid to the silica sol is (0.3 to 5):
1. The hydrophobic agent includes one of perfluorononanoic acid, perfluoropolyether, perfluorodecyltrialkoxysilane, and perfluorooctyltrialkoxysilane.
8. The preparation method according to claim 2, characterized in that: In the step (2), the preparation step of silica sol comprises: dissolving siloxane in a mixed solution of ethanol and water, adding ammonia solution and stirring to obtain silica sol; the siloxane comprises one of methyltriethoxysilane, ethyl orthosilicate, and methyl orthosilicate; the volume ratio of ethanol to water in the mixed solution of ethanol and water is (1-15):1, and the volume ratio of siloxane to the mixed solution of ethanol and water is (0.1-1):
1.
9. The preparation method according to claim 2, characterized in that: In the step (3), the drying temperature is 50-100° C., the drying time is 6-15 hours, the roasting temperature is 200-500° C., and the roasting time is 2-6 hours.
10. An application of a copper-zinc-zirconium-silicon catalyst having a hydrophobic surface, characterized in that: The copper-zinc-zirconium-silicon catalyst described in claim 1 or the copper-zinc-zirconium-silicon catalyst prepared by the preparation method described in claims 2 to 9 is used to catalyze the hydrogenation of carbon dioxide to produce methanol.
Citation Information
Patent Citations
Preparation method of copper-zinc-aluminum-molecular sieve catalyst for catalyzing CO2 hydrogenation to prepare methanol
CN116393160A